The interaction mechanism, conformational changes and computational simulation of the interaction between surface layer protein and mannan at different pH levels. (30th March 2023) - Fu, Mengqi; Mi, Si; Zhao, Jinrong; Wang, Xianghong; Gao, Jie; Sang, Yaxin
Graphical abstract: Highlights: Interaction mechanism between SLP and mannan at different pH were firstly studied. The quenching of SLP by mannan were mainly static quenching at pH. The binding stability of SLP with mannan at pH 5.0 was stronger. The structure and conformation of SLP were changed after binding to mannan at different pH. The interaction at different pH resulted in changes in binding force between SLP and mannan. Abstract: The aim of this study was to explore the interaction mechanism between surface layer protein (SLP) and mannan at pH 3.0, 5.0 and 7.0 through multi-spectral methods combined with computer simulations. The fluorescence quenching data showed that SLP and mannan bound spontaneously to form complexes at all pH levels. In addition, molecular docking revealed that SLP had different binding sites to mannan at different pH, which mainly depended on hydrogen bonds and hydrophobic interactions. Molecular dynamics simulation results showed that the combination with mannan contributed to the stability of SLP structure. This study confirmed that the combination of SLP and mannan at pH 5.0 has higher binding affinity and more stable structure. The mechanism proposed in this study provides understanding underlying the interactions between SLP and mannan and insights for further exploration of the potential of SLP as a mannan transport carrier in fermented dairy products similar to TKM.